Pengaruh Kualitas Layanan Dan Kepuasan Terhadap Loyalitas Nasabah Bank Bri Unit Makassar - Muchlis Abbas (Program Pascasarjana STIE Amkop Makassar, 2023)
To analyze and analyze the quality of service discipline influential work in the satisfaction of the performance of customers of Bank Rakyat Indonesia Unit Makassar. It is also to study and analyze the variables which have a dominant influence on the satisfaction of customers of Bank Rakyat Indonesia Unit Makassar Population in the study were all clients of BRI Unit Makassar Makassar. Sampling dilakukakan with the consideration that the population is very large in number so as in the form of a representation populasi.Analisa data used to test the hypothesis of the research is to use random sampling techniques The results showed that the quality of service is a significant effect on the satisfaction of the Customer, in this case the Bank BRI branch Somba OPU has performed increasingly maximum in showing the quality of service is the best, the same thing also confirmed the results of previous studies that the quality of service is an effect on customer satisfaction Quality of service indirectly contribute significant and positive impact on customer loyalty. Customer satisfaction the intervening variable also showed significant results and in supporting factor of customer loyalty Kata Kunci: Service, Customer, Loyalily